Managerial Accountability in Village Fund Management - Ida Hayu Dwimawanti; Amni Zarkasyi Rahman; Rafa’ Fazlur Rahman (Faculty of Social and Political Sciences, Universitas Diponegoro, 2019)
Village Funds are funds sourced from the State Revenue and Expenditure Budget intended for villages which are transferred through the district revenue and expenditure budget and then channelled to the village treasury account and used to finance the implementation of development and community empowerment. The Village Fund has village development goals, namely improving the quality of human life, improving village welfare, and reducing poverty. This study aims to analyze the Managerial Accountability of Village Fund Management in Rejosari Village, Pringsurat Subdistrict, Temanggung Regency. This study used qualitative research methods with eight informants as the research subject. The results of the study show that the Managerial Accountability of Village Fund Management in Rejosari Village, Pringsurat Subdistrict, Temanggung Regency has not demonstrated effective results. Several indicators of Managerial Accountability that have not been implemented optimally further support this conclusion. Meanwhile, the factors that influence accountability such as the personal factor, leadership factor, team factor, and contextual factor are sufficient, although obstacles are still apparent. Based on this conclusion, the researchers recommended the village fund administrators to be highly committed and maximizing the support of existing resources to the maximum.